GAMBARAN PENGETAHUAN IBU PRA MENOPOUSE (USIA 40-44 TAHUN) TENTANG MENOPOUSE DI DESA GEMBONGAN KECAMATAN SIGALUH KABUPATEN BANJARNEGARA - Anatria Septama Putri; Feti Kumala Dewi; Murniati Murniati (Viva Medika, 2010)
Menopause is a process of transition from a productive period heading slowly to the non-productive time due to reduced estrogen and progesterone. When a person enters thepre-menopausal age, physical and psychological changes occur. Due to lack of knowledgeof women about menopause, the majority of women experience anxiety due to the physicalchanges that occur during menopause. The village is the highest village first Gembongannumber of women aged 40-44 years as many as 114 people. Based on a preliminary surveyof the 10 mothers aged 40-44 years as many as 4 out of menopause but the mother said asmany as six people do not know. This research is quantitative descriptive study, with crosssectional, population in this study were mothers of pre-menopausal (ages 40-44 years) inthe village Gembongan Sigaluh District of Banjarnegara district. until the time of the study,namely 114 ibu.Teknik study using simple random sampling technique, by the way whipped54 people. The data used are primary data in the form of a questionnaire that was tested forvalidity and reliability. Analysis of the form of the univariate analysis in the form of distrusifrequency. The results showed the mother's knowledge of pre menopause mostly haveenough knowledge that 26 respondents (48.1%), the majority of respondents who have agood knowledge of socio-economic <730.000, - as many as five respondents (71.4%), themajority of respondents knowledgeable both have a college education is as much as threerespondents (100%), the majority of respondents were knowledgeable either obtaininformation from sources of documentary information as much as 2 respondents (100%)with good knowledge. Keywords: knowledge, maternal pre-menopause, menopause